Tata Kelola Dana Zakat Berbasis Transparansi dan Akuntabilitas: Studi pada UPZ Masjid Miftahul Huda - Yulia, Mukhafatul Sifa; Purwanto; Rifai, Fuad Yanuar Akhmad (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the governance of zakat funds at the Zakat Collection Unit (UPZ) of Miftahul Huda Mosque, with an emphasis on the implementation of transparency and accountability principles. Using a qualitative case study approach, data were collected through in-depth interviews with UPZ administrators and several zakat payers (muzaki), as well as documentation analysis of financial reports. The results indicate that the UPZ has established a governance structure covering the planning, implementation, distribution, and utilization of zakat funds. The UPZ has also implemented managerial transparency through the existence of standard operating procedures (SOPs), an organizational structure, and activity reporting. However, financial transparency—particularly in publishing financial reports to the public—remains suboptimal. In terms of accountability, financial records have been maintained in a detailed and systematic manner, yet openness of these reports has not been fully realized. These findings highlight the need to strengthen publication strategies and involve zakat payers in the evaluation process to enhance the professionalism and credibility of zakat fund management.